Ten new species of lichenized Basidiomycota in the genera Dictyonema and Cora (Agaricales: Hygrophoraceae), with a key to all accepted genera and species in the Dictyonema clade - Lücking, Robert; Dal-Forno, Manuela; Lawrey, James D.; Bungartz, Frank; Rojas, María E. Holgado; Hernández M., Jesús E.; Marcelli, Marcelo P.; Moncada, Bibiana; Morales, Eduardo A.; Nelsen, Matthew P.; Paz, Elias; Salcedo, Luis; et al. (Phytotaxa, 2013)
As part of a larger systematic and taxonomic revision, including molecular phylogenetic analysis, of lichenized Basidiomycota in the Dictyonema clade, ten species are described as new from tropical America, seven in the foliose genus Cora and three in the filamentous genus Dictyonema: Cora arachnoidea J. E. Hern. & Lücking, sp. nov., C. aspera Wilk, Lücking & E. Morales, sp. nov., C. byssoidea Lücking & Moncada, sp. nov., C. cyphellifera Dal-Forno, Bungartz & Lücking, sp. nov., C. inversa Lücking & Moncada, sp. nov., C. squamiformis Wilk, Lücking & Yánez-Ayabaca, sp. nov., C. strigosa Lücking, E. Paz & L. Salcedo, sp. nov., Dictyonema aeruginosulum Lücking, Nelsen & Will-Wolf, sp. nov., D. diducens Nyl. ex Lücking, sp. nov., D. metallicum Lücking, Dal-Forno & Lawrey, sp. nov., and D. obscuratum Lücking, Spielmann & Marcelli, sp. nov. We discuss the taxonomic status of the six names historically established for species belonging in the genus Cora and reinstate the names C. gyrolophia Fr., C. pavonia (Sw.) Fr., and C. reticulifera Vain., providing diagnostic features for these, whereas the status of C. glabrata (Spreng.) Fr. and C. bovei Speg. remains uncertain. The following new combinations are introduced: Cora hirsuta (Moncada & Lücking) Moncada & Lücking, comb. nov., C. minor (Lücking, E. Navarro & Sipman) Lücking, comb. nov., Corella melvinii (Chaves, Lücking & Umaña) Lücking, Dal-Forno & Lawrey, comb. nov., Cyphellostereum phyllogenum (Müll. Arg.) Lücking, Dal-Forno & Lawrey, comb. nov., Dictyonema caespitosum (Johow) Lücking, comb. nov., D. irrigatum (Berk. & M. A. Curtis) Lücking, comb. nov., D. phyllophilum (Parmasto) Lücking, Dal-Forno & Lawrey, comb. et stat. nov., and D. scabridum (Vain.) Lücking, comb. et stat. nov. Keys are presented to the five currently accepted genera and 40 currently recognized species in the genera Cyphellostereum, Dictyonema, Cora, and Corella.